Financial Performances and Public Procurement Loss: Indonesia Ministries/State Study - Rosinta H. F. Purba; Amirullah S. Hardi (Jurnal Ikatan Sarjana Ekonomi Indonesia, 2020)
Transparency of public acquisition is one of the core mechanisms in combating corruption. However, in Indonesia, despite the transparency of audit results of the Ministry/State Agency’s financial statement related to Unqualified Opinions published by the State Audit Agency has increased yearly, the trends of corruption cases increased as well. This research aims to investigate the determinants of financial performances and the state financial loss using panel data of 74 Indonesia ministries/state agencies between 2014-2016, further employing the random effects analysis to overcome serial correlation. The main findings indicate that unqualified opinion positively and significantly reduces the state financial loss in Indonesia. Besides, political party leadership (non-independent Minister) significantly influenced the state financial loss. Furthermore, capital expenditure and state expenditure allocation significantly influenced the state financial loss in Indonesia while accountability score was not important determinants of financial loss in Indonesia.